Evaluation of Enzymes Liver and Kidney Function in Serum People the Exposures at Risk of Chemicals Volatile in the Lab Pharmaceutical Samarra - Methaq N. Mahmood (Journal of Global Pharma Technology, 2016)
Included the present examination procedure of making sense of the value, sum, or nature of something of certain numbers that change identified with the synthetic substances in living things in the squandering almost no while working or delivering something of the functions of the liver represented by the enzymes ALT and AST and organ that creates urine represented by the creatinine and the Uric acidin blood of people workers in the public company for medicine Samarra from exposure at risk of materials chemical dangerous and unstable used in the making of medicine compared of people non-workers as a group control in the city of Samarra, a total of 60samples 30samples from workers in the public company for medicine Samarra from exposure at risk of materials chemical dangerous and unstable 30 control non-workers group their ages ranged from 30 to 45 years, and after the separation of serum managed and did/done tests (related to the chemicals in living things) own research. Results showed big increased(P˂0.05) at levels of the enzymes ALT and AST in the group exposure at risk of materials chemical dangerous and unstable as compared with the control group, As showedresults increased (a lot)( P˂0.05) at levels of the creatinine in the group exposure at risk of materials chemical dangerous and unstable as compared with the control group, Whereas the Uric acid had a big drop in group exposure at risk of materials chemical dangerous and unstable as compared with the control group.Keywords: Exposed volatile chemical, ALT, AST, Creatinine, Uric acid